Avaliação clínica da efetividade de mascaramento de manchas fluoróticas: microabrasão x infiltração resinosa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This study evaluated the masking capability of fluorosis stains using the microabrasion technique in comparison to the resin infiltration technique. Method: Twenty patients, from 12 to 16 years old, presenting fluorosis stains on dental enamel were randomly divided into two groups (n = 10): microabrasion and resin infiltration. Both techniques were performed according to the manufacturer's guidelines. The evaluation occurred in three different ways: quantitative, qualitative and "Degree of patient/responsible satisfaction". Standardized photographs were taken (baseline and 1 week after the intervention), to be analyzed using Adobe Photoshop CS5 software, to obtain the data for calculating the values of ΔL, Δa, Δb and ΔE at the points where the spot of fluorosis was more intense in each of the treated teeth. To evaluate the aesthetic optimization, by qualitative/satisfaction degree, obtained in the fluorotic stains, two blind and calibrated evaluators were based on the same paired images (baseline and 7 days after the intervention) used in the quantitative analysis, recording in a visual perception scale (VAS) values between "1" (No improvement in appearance or injury not completely removed), to "7" (Exceptional aesthetic improvement, or stain totally removed); patients and/or parents were asked to indicate their satisfaction degree, in the same VAS scale used by the evaluators, who ranged from “1” (totally dissatisfied) to “7” (exceptionally satisfied). The data of the quantitative analysis were submitted to statistical analysis by Student's “t” Test and those of the qualitative analysis Fisher's Exact Test (α = 0.05). Results: There was no significant difference between groups when the objective measurements were considered (values ΔL, Δa, and Δb ΔE) (p> 0.49). Regarding qualitative evaluation, patients were completely satisfied by 88% and 100% of the cases, respectively, to techniques and microabrasion resin infiltration (p = 0.42). However, investigators found that the resin infiltration completely changed the aesthetic appearance of teeth in 70% of cases, while it occurred in only 10% of cases when the microabrasion was applied (p = 0.02). Conclusion: The both techniques (microabrasion and resin infiltration) were able to remove/mask fluorosis stains and promoted a high level of patient satisfaction, due to a greater dental structure preservation in the resin infiltration technique, both techniques obtained aesthetics results although positive differences were observed in favor of resin infiltration.
Clinical evaluation of fluorotic stains masking capability: microabrasion x resin infiltration
Keywords: Estética; Fluorose do esmalte; Infiltração resinosa; Microabrasão; Micro invasivo; Enamel fluorosis; Esthetic; Resin infiltration; Micro abrasion; Micro invasive; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA